APLIKASI PERAMALAN JUMLAH KELAHIRAN DENGAN METODE JARINGAN SYARAF TIRUAN - Safira Amudya Nurdela (Universitas Airlangga, 2017)
The forecast is a statistic analysis to predict what it will happen in the future using the data and information from the past. This research aimed to apply Artificial Neural Network method for estimate the f ertility rate in Surabaya. The study was descriptive which using secondary data providing from Dinas Kesehatan Kota Surabaya. The study used time series data by recapitulation of fertility rate monthly from 2012-2016. The data analysis used R Program. The result showed the best estimator model for Artificial Neural Network method was 1-3-1 architecture with preprocessing normalized. RMS value of Artificial Neural Network method was 338.1551. The conclusion of this research was the Artificial Neural Network method for estimate the f ertility rate in Surabaya could be used for planning birth control program especially Badan Kependudukan dan Keluarga Berencana Nasional.